Biobehavioral Framework of Symptom and Health Outcomes of Uncertainty and Psychological Stress in Parkinson Disease. Issue 6 (December 2016) - Austin, Kim W.; Ameringer, Suzanne W.; Starkweather, Angela R.; Cloud, Leslie J.; Sturgill, Jamie L.; Elswick, Ronald K.
Abstract : ABSTRACT: Parkinson disease (PD) is a debilitating, progressive neurodegenerative disorder characterized by complex motor and nonmotor symptoms that fluctuate in onset, severity, level of disability, and responsiveness to treatment. The unpredictable nature of PD and the inability to halt or slow disease progression may result in uncertainty and psychological stress. Uncertainty and psychological stress have important implications for symptom and health outcomes in PD. Uncertainty and psychological stress have been shown to worsen symptoms, functional capacity, and quality of life in chronic illnesses; however, the causal mechanisms have yet to be elucidated. We propose a biobehavioral framework for examining uncertainty and psychological stress in PD. The framework considers factors that may contribute to uncertainty and neuroendocrine–immune mechanisms of uncertainty and psychological stress that may influence symptom and health outcomes in PD, for the ultimate purpose of improving symptom and disease progression, functional capacity, and quality of life.